Seasonality of calving in Jaffarabadi buffaloes - SN Ghodasara; KS Murthy; PU Gajbhiye; AR Ahlawat (Journal of Livestock Biodiversity, 2025)
The pattern of calving in Jaffarabadi buffaloes was analysed in an organized farm. Calving records of 616 Jaffarabadi buffaloes were used. Season and month had significant (p<0.01) effect on calving. Calving frequency was higher during rainy season (45.45%) in Jaffarabadi buffalo followed by autumn (23.86%). Lowest percentage of calving (7.31) was observed during summer season. September (18.02) and August (15.58) had maximum percentage of calving followed closely by October (14.61%). July, November, December and January months recorded 11.85, 9.25, 7.63 and 5.51 % of calving, respectively. Pattern of calving is similar to other breeds of buffaloes throughout the country and photoperiodicity seemed to play greater role in influencing season of calving.